Experimental study and resilience modeling for prefabricated hollow diaphragm walls of full-assembled underground stations under urban multi-disturbance conditions. (May 2023) - Qiu, Tong; Sun, Xiaohui; Chen, Xiangsheng; Su, Dong; Zhang, Jiqing; Xu, Zhenyan; Song, Ran; Wang, Xiuyan
Graphical abstract: Highlights: The first application of a novel prefabricated hollow diaphragm wall was presented. The recoverability and ductility of PHDW was revealed foremost through experiments. PHDW recoverability enhanced the deformation tolerance of single-walled structures. PHDW-HRAF combining monitoring constituted a novel real-time assessment technique. Multi-disturbance monitoring strategies was proposed for PHDWs. Abstract: A full-assembled underground station (FUS) using a prefabricated enclosure structure and prefabricated main structure was constructed for the first time in the Shenzhen Metro. The key technology of an FUS is the use of single-walled prefabricated diaphragm walls instead of traditional overlapping cast-in-situ diaphragm walls and exterior walls. To improve the applicability of a single-walled diaphragm wall for an FUS, this study proposed a novel prefabricated hollow diaphragm wall (PHDW) and investigated its response and resilience to urban multi-disturbance conditions. First, full-scale recoverability and ultimate bearing experiments were performed on the PHDWs. Second, a PHDW hierarchical resilience assessment framework was established. Third, a multi-disturbance finite element analysis (FEA) was performed on the Shenzhen Metro FUS using PHDWs. Based on above, a security management strategy was proposed. The main conclusions are as follows: (1) The recoverability and ultimate bearing experiments revealed that the PHDW had both recoverability and ductility. (2) The FEA indicated significant variability in the multi-disturbance response of the PHDWs. Therefore, a rigid deformation control is inappropriate for the security management of PHDWs. (3) The disturbance deformation tolerance of a single-walled enclosure structure can be improved by approximately 20 %–60 % by using PHDW recoverability. (4) Multiple conditions of poor resilience must be fully alerted using a multi-disturbance monitoring strategy. This study provides a security management strategy for Shenzhen Metro FUS and facilitates the low-carbon construction of urban traffic facilities.